Lived Experiences of Women Who Underwent Induced Abortion: A qualitative study of Rakai District, Uganda - Joy Margaret, Nalubega; Kizito, Omona (International Journal of Health, 2021)
Background: Induced abortion is one where products of conception are expelled before 28 weeks of gestation. The process can be safe or unsafe. Safe termination of pregnancy is performed by skilled persons using appropriate tools whereas unsafe induced abortion is performed either by persons without the necessary skills or in an environment without the minimum medical standards, or both.Objectives: To explore the lived experiences of women who had induced abortion in Rakai DistrictMethodology: Phenomenological qualitative design was used. Study population was women who underwent induced abortion. 25 women who had induced abortions in past 1-3years were interviewed. Data was collected by in-depth interviews, tape recorded; transcribed verbatim and written in note book.Results: Lived experiences included denial, shame, confusion, fear, anger, anxiety, depression and uncertainty. Participants reported use of local herbs like â€œekiwokoâ€ and â€œmajaaniâ€, â€œetwaataâ€, â€œkisuulaâ€ and roots of sugar canes, among others, to induce abortion. The processes were mostly traditional, associated with: severe pain, heavy bleeding, and so on. They were life-threatening and horrible. Short- and long-term lived experiences included secondary barrenness, depression, crying-in-privacy and regrets, among others.Conclusion: Health workers and women in child-bearing age need to work together to discuss how to control unplanned pregnancies.Â